A lei Maria da Penha entre o direito formal e o direito de fato: a necessidade de formação permanente da rede de proteção às mulheres em situação de violência doméstica no estado do Tocantins - Lourenço, Edssandra Barbosa da Silva (Universidade Federal do Tocantins, 2016)
Domestic violence against women is an old phenomenon, which occurs in world affairs and in all social classes without distinction. It is a phenomenon with multiple determinations, whose roots imply recognition that history produces and reproduces these conditions with different shapes and shades, according to each culture as a historical building. In Brazil, for a long time, did not give due emphasis to the fight against domestic violence against women. The Federal Constitution of 1988 was a milestone in this matter to establish equality between men and women and give the State the creation of mechanisms to suppress violence within the family relationships. However, only with the advent of Law. 11.340 / 06, called Maria da Penha Law ─ fruit of the struggle of organized women's movements ─ was that the Brazilian State jumped into the effective fighting domestic and family violence against women. The objective of this work, however, is to produce arguments to show that the full implementation of the law still depends on several factors, highlighting the need for ongoing training of all professionals working in the safety net for women in domestic violence situations or family. The gap between the formal law and the fact right there, not for failing to Maria da Penha Law, but due to the unpreparedness of own network of assistance to women in situations of violence, the lack of investment in prepared police authority and specialized to deal with the situation, the sense of impunity felt by the perpetrators, among countless other factors that compromise the effectiveness of the law. The violation of human rights in this sense occurs every day in different Brazilian cities even have conditions to meet 7 the cases requiring urgent protection. From the historical problem of contextualization we observed that, in essence, the debate undertaken highlighted the urgent need not only to combat violence against women, but to provide means and instruments to execute the law, starting with the continuing education of all personnel designated to attend cases, guiding the victims and endorsing their rights with immediate protection measures and assistance. Ongoing formation is just a way of coping, foreseen in the legislation.